The effect of combination therapy of sulfonylurea, metformin, and acarbose in type 2 diabetes mellitus patients - Tri Murti Andayani; Mohamed Izham Mohamed Ibrahim; Ahmad H. Asdie (Indonesian Journal of Pharmacy, 2009)
Diabetes mellitus is a complex disorder that involves multiple pathophysiological defects. As the disease progresses, further functional decline in β-cell is apparent. In most cases, patients on oral antidiabetic therapy will require not only an increase in dose, but also the addition of a second or third oral agent. The aim of this study was to evaluate the effectiveness and safety of triple therapy with sulfonylurea, metformin, and acarbose in patients with poorly controlled glycemia. The study design was a prospective observational study in 49 type 2 diabetic patients followed in Department of Endocrinology RSUP Dr Sardjito Indonesia from May 2007 to September 2008. Patients with hypertension were included if their blood pressure was well controlled with antihypertensive medication. All patients with documented gastrointestinal disease were excluded. At baseline and at 3-month intervals, levels of HbA1C, fasting and postprandial plasma glucose, hypoglycemic episodes, and edverse event were evaluated. Fourty nine patients, 22 men and 27 women, aged 62.84 +7.85 years, diabetes duration of 11.92 +6.09 years were studied. The initial HbA1C level was 8.08 +1.89 % which significantly increased to 8.73 +2.37 % (p<0.05). Only 32.98 % of subjects achieved target value of HbA1C (≤ 7 %). Fasting and post-prandrial plasma glucose values were increased from 160.39 +60.25 mg/dL to 170.71+56.60 mg/dL and 210.31+ 75.88 mg/dL to 218.67 +75.03 mg/dL respectively, but not significantly different. Acarbose was more frequently associated with flatulence (46 %) and abdominal bloating (12 %), metformin with flatulence (12 %), nausea (14 %), diarrhea (2 %) and abdominal discomfort (6 %). In conclusion, combination therapy of sulfonylurea, metformin, and acarbose in type 2 diabetic patients with poorly controlled glycemia can cause the additive risk of adverse events.Key words : triple therapy, glycemic control, type 2 diabetes mellitus